2019
DOI: 10.1002/cyto.a.23882
|View full text |Cite
|
Sign up to set email alerts
|

Rigor and Reproducibility of Cytometry Practices for Immuno‐Oncology: A multifaceted challenge

Abstract: The rapid advancement of immunotherapy strategies has created a need for technologies that can reliably and reproducibly identify rare populations, detect subtle changes in modulatory signals, and assess antigenic expression patterns that are time-sensitive. Accomplishing these tasks requires careful planning and the employment of tools that provide greater sensitivity and specificity without demanding extensive time. Flow Cytometry has earned its place as a preferred analysis platform. This technology offers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…To sum up, the aforementioned result proves that the proposed AuNPs–GO–anti-IgG probe has good stability and repeatability that allows the preparation of the sensing probes without a tight schedule. For long-term storage purposes, numerous studies in the literature have reported convenient and widely used methods for long-term storage of proteins [ 38 , 43 , 44 , 45 , 46 , 47 ]. These preservation methods will be explored in our future sensor prototype development to improve preservation time and stability.…”
Section: Resultsmentioning
confidence: 99%
“…To sum up, the aforementioned result proves that the proposed AuNPs–GO–anti-IgG probe has good stability and repeatability that allows the preparation of the sensing probes without a tight schedule. For long-term storage purposes, numerous studies in the literature have reported convenient and widely used methods for long-term storage of proteins [ 38 , 43 , 44 , 45 , 46 , 47 ]. These preservation methods will be explored in our future sensor prototype development to improve preservation time and stability.…”
Section: Resultsmentioning
confidence: 99%
“…The recent Cytometry Part A Special Issue: Rigor and Reproducibility highlighted the importance of antibody validation, sample preparation and instrument, assay and post‐analysis standardization [21–23]. These practices are indispensable to successful analytical performance or complete validation of high‐dimensional assays.…”
Section: Discussionmentioning
confidence: 99%
“…The use of any type of cytometry technology for longitudinal cancer immunotherapy studies requires reproducible protocols with careful standardization of every step in the workflow, from experimental and panel design to sample handling/acquisition and data analysis, to obtain reliable results (Laskowski et al, 2020). Multiple challenges can be faced during the implementation of cytometry in immune monitoring studies: gating and analysis subjectivity; operator level of training; instrument maintenance and QC; lack of protocol consistency; lack of optimized controls; and technical errors during staining, acquisition or data analysis and interpretation.…”
Section: Challenges In the Implementation Of Flow Cytometry For Immune Monitoringmentioning
confidence: 99%